Relevance meaning in Malay and Spanish text - Husain, Salina; Darmi, Ramiza; Syed Abdullah, Syed Nurulakla; Danuri, Norazmi (Human Resource Management Academic Research Society, 2020)
One of the obstacles in translating process is the grammatical structural difference between source language to target language. Therefore, this paper discussing meaning relevance in text translation in order to discover similarities and differences meaning between Malay and Spanish. The researcher has focused on four sentences from Malay to Spanish by using A1, A2, A3 and A4 label involving ten students from Universiti Putra Malaysia who taking Spanish as an elective course. The Relevance Theory (1986 and 1995) by Sperber and Wilson’s is use in this paper. The objectives are to discuss translation equivalents for textual verb expressions from Malay to Spanish, and to analyse the translation equivalents based on their fuctional similarities and differences to ensure the meaning conveyed remain the same to the original text. Findings from this research can assist the teaching and learning of Spanish as a foreign language specifically in verb formation.